Financial Performance of Local Governments Before and After Refocusing and Budget Reallocation Policy for Handling Covid-19 In Indonesia - Hasna Athiya Putri; Rindu Rika Gamayuni; Fitra Dharma (Jurnal Akuntansi Bisnis, 2023)
The pandemic of COVID-19 requires all levels of government to take action under a broad context of economic uncertainty and social pressures. In Indonesia, a policy of refocusing and reallocating the budget is implemented as a regional government action to overcome the impact of Covid-19. The purpose of this research is to examine the impact of refocusing and budget reallocation policies on the fiscal health of Indonesian municipalities in the wake of the Covid-19 outbreak. The sample in this study uses districts and cities in Indonesia. The Regional Government Financial Reports for 2018 and 2019 represent the pre-refocusing and budget reallocation years, then 2020 and 2021 as the years and post-refocusing and budget reallocation. Using the independence and effectiveness ratios, the results demonstrate that pre- and post-refocusing and budget reallocation regional governments differed significantly in their financial performance. The efficiency ratio, however, shows no change between the pre-and post-refocusing and budget reallocation.